(untitled) (Bangladesh Journal of Plant Taxonomy, 2021)
Bangladesh lies in Indian subcontinent, an area rich in Pteris species. However, so far there is no modern account on the species diversity of Pteris in Bangladesh. Based on a thorough study of literature and limited specimens available to us, we currently recognize 15 species of Pteris in Bangladesh. Among these species, P. giasii is currently known only from Bangladesh; P. longipinnula, which has not been collected since 1858, was recently rediscovered in Sylhet. Pteris cretica, P. pellucida, P. quadriaurita var. quadriaurita, and P. quadriaurita var. setigera are excluded for the fern flora of Bangladesh. To facilitate the recognition of species, a key to species and brief notes for each species are provided. Bangladesh J. Plant Taxon. 28(1): 131-140, 2021 (June)